PRISTINA’S DEVELOPMENT STRATEGY OF 2013-2016: AN ANALYSIS OF THE SITUATION IN THE EDUCATIONAL, CULTURAL, YOUTH, AND SPORT SECTOR - Krasniqi, Sokol; Krasniqi, Enver H. (European Scientific Journal, ESJ, 2015)
Sustainable economic development is done through Development Strategy. Development strategies have some priorities which include encouraging other participants, stakeholders, and those that have impact on the investment to act in accordance with the vision. This is accomplished by working together to establish priorities in the correct way. Also, this is undoubtedly the key to success. Economic development is essential for the survival of all municipalities. Economic growth which is accomplished as a result of an economic development plan, promotes new capital in municipalities. Hence, this is becoming an integral part of the strategic process at the national level. This enables the creation of a better environment and economic competition locally. Local economic development is the process by which local communities (public, businesses, and non-governmental organizations) are working towards the achievement of sustainable economic development and provides an increased level of employment, welfare, and quality of life for all (World Bank, 2009). Local economic development is one of the most important areas to increase the quality of life of the citizens and create a favourable environment for business development (Riinvest, 2002). Development Strategy comes as a response to rapid changes, keeping containment conditions by which interest groups will have the constructive approach in evaluating the situation. Also, the position towards the strategy which takes the specific actions is placed into consideration. This therefore ensures that the changes in the city are not dramatic. Municipalities must learn how to compete and how to deploy themselves in order to ensure quality of life, jobs, and services, which then influences the attraction of investments. Strategy is often a prerequisite for financing municipal projects through government grants, FDI, banks, publicprivate partnerships, or EU funds. During this process, the municipality creates partnerships, both within and outside the municipality. The stronger these partnerships are, the greater the chances of a municipality to secure future development. The strategy in itself provides the opportunity for the community to continuously improve the investment climate. It is a general observation that development strategy should have no overarching plan. Furthermore, it must contain some strategic steps in order for it to increase the system as a whole. Thus, this is done through the mechanisms of different national levels such as changes in the status of the city, public and private investment, public-private initiatives etc.